Safety and quality self-evaluation tool for food industry - N. A. H., Jamari; Hanida, Abdul Aziz (Penerbit Universiti Malaysia Pahang, 2023)
Food safety and hygiene are crucially important in any baking industry. The absence of knowledge, attitude, and good practices among food workers has led to concerns over food safety in the modern era. The food industry faces increasing regulatory pressures and consumer demands for safe, high-quality products. To reduce the cases and issues in the food industry related to food contamination in the bakery industry, the evaluation will help determine the relationship between knowledge and good hygiene practices in food handling and the level of hygiene evaluation in food industry quality in food handling processes. The primary objective encompassed constructing a robust framework grounded in established legislation and developing a self-evaluation tool. Two experts in food safety participated in the content validation of the safety and quality self-evaluation tool. The scale-level content validity index (CVI) based on the average method is 0.97. These indicate that most of the items in the developed safety and quality self-evaluation tool meet the satisfaction levels of both experts. A case study was conducted to gain feedback using the System Usability Scale (SUS). The findings from the usability study indicated a marginal acceptability of the tool with an overall average SUS score of 66.25%.